“Los Cambios Conductuales Y Su Incidencia En El Rendimiento Académico De Los Estudiantes De Básica Superior De La Unidad Educativa “Carlos Alberto Aguirre Avilés”, De La Parroquia La Unión, Cantón Babahoyo, Provincia De Los Ríos”. - Murillo Murillo Zulema Yolanda (2015)
This research work with a quantitative approach, is done in order to recognize the impact that generate behavioral changes on the academic performance of students, for which data collection techniques based on media and formal instruments are used, using systematic processes in recording observations, interviews and surveys that provide data to study and analyze the facts. The study was carried out in the Education Unit Aviles Carlos Alberto Aguirre, of the parish of La Union, Los Rios province, where the authorities, teachers, parents, families and students in higher basic education, which are the subject matter involved, benefiting the entire educational community, since several behavioral aspects of students that one way or another influence the development of educational activities and thus directly or indirectly affect the performance they show in the classroom were analyzed. There is a large conglomerate of theoretical analysis and references that are typified in the current investigation that give answers to the problems of the study. Furthermore, a strategic proposal to maintain behaviors that benefit the student in all areas of your life, both educational and staff, substantially improve their academic performance was raised.